2015
DOI: 10.1186/s12889-015-2073-y
|View full text |Cite
|
Sign up to set email alerts
|

Do body mass index trajectories affect the risk of type 2 diabetes? A case–control study

Abstract: BackgroundAlthough obesity is a well-studied risk factor for diabetes, there remains an interest in whether “increasing body mass index (BMI),” “high BMI per se,” or both are the actual risk factors for diabetes. The present study aimed to retrospectively compare BMI trajectories of individuals with and without diabetes in a case–control design and to assess whether increasing BMI alone would be a risk factor.MethodsUsing comprehensive health check-up data measured over ten years, we conducted a case–control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
1
5
1
Order By: Relevance
“…Higher insulin secretion and lower insulin sensitivity was reported in obese than leanT2DM patients (Sone et al 2003). In the male and female patients with T2DM, significantly higher BMI is observed in the present study as against the gender specific controls, which is in contrast to the study in which no significant difference was observed in Japan (Mano et al 2015). Weight gain and consequent increase in BMI and obesity in patients with T2DM may be due to aging associated increase in fat mass, decreased physical activity, poor diet, usage of antidiabetic drugs such as sulphonylurea, thiazolidinediones and insulin and weight loss was shown to improve glycemic control (Daousi et al 2006;Hills et al 2010;Kamath et al 2011).…”
Section: Type 2 Diabetescontrasting
confidence: 99%
“…Higher insulin secretion and lower insulin sensitivity was reported in obese than leanT2DM patients (Sone et al 2003). In the male and female patients with T2DM, significantly higher BMI is observed in the present study as against the gender specific controls, which is in contrast to the study in which no significant difference was observed in Japan (Mano et al 2015). Weight gain and consequent increase in BMI and obesity in patients with T2DM may be due to aging associated increase in fat mass, decreased physical activity, poor diet, usage of antidiabetic drugs such as sulphonylurea, thiazolidinediones and insulin and weight loss was shown to improve glycemic control (Daousi et al 2006;Hills et al 2010;Kamath et al 2011).…”
Section: Type 2 Diabetescontrasting
confidence: 99%
“…Previous studies, including the Bogalusa Heart Study, have indicated that glucose and insulin levels during adolescence are mediated by these factors, independent of adiposity [2325]. The findings from this and previous studies suggest that adolescence is a critical temporal window for BMI control to reduce the risk of adult hyperglycaemia [11, 1316, 2629]. …”
Section: Discussionsupporting
confidence: 50%
“…A few previous studies have investigated associations between BMI trajectories and diabetes incidence [23][24][25][26], diabetes-related metabolic markers, or inflammatory markers [27][28][29][30]. Findings from these studies indicate that risks for diabetes incidence, diabetes-related metabolic markers (i.e.…”
Section: Discussionmentioning
confidence: 99%